The Use of Inquiry-Based Learning Strategy in Teaching Writing Skill for the Eighth Grade Students Junior High School - Hidayatul Isra'; Maman Asrobi (VELES Voices of English Language Education Society, 2018)
This present study investigated the use of inquiry-based learning strategy in teaching writing skill for the eighth grade students of MTs. NW Dames in the school year 2016-2017. Research methodology that was used in this study was pre-experimental research and the design was a one group pretest and posttest design. The population was eighth grade students consisted of two classes and took one class as the sample. The sampling technique in this study was cluster random sampling. The data collection was done by administering pre and post-test to the eighth grade students of MTs. NW Dames (21 students). Then to analyze the data, the present researcher used a paired samples t-test by using SPSS 22 for windows. Based on the data analysis, the present researcher found that the mean score of pre-test was 59.14 and post-test was 63.62, it could be stated that null hypothesis was rejected and the hypothesis was accepted. Inquiry-based learning strategy was significantly effective in teaching writing skill for the eighth grade students of MTs. NW Dames in the school year 2016-2017. Considering the process and the results of this research, the present researcher suggested that English teacher can use inquiry-based learning strategy to teach students.